The Anglo-American and Commonwealth Negotiations for a Zimbabwean Settlement between Geneva and Lancaster, 1977–1979. Issue 5 (3rd September 2017) - Scarnecchia, Timothy
ABSTRACT: As historical interest and scrutiny has grown over the diplomatic history of the Rhodesian crisis from the mid-1970s to independence in 1980, the bulk of historical attention has been focused on the two big conferences in this period, the Geneva talks in October–December 1976, and the Lancaster House talks in September–December 1979. This article examines the shifting contours of Anglo-American negotiations with the leaders of the Zimbabwean Patriotic Front (Joshua Nkomo and Robert Mugabe), the Front Line State presidents, the South African government and the UDI government of Ian Smith in this important period between Geneva and Lancaster House. This article begins by examining the rivalry between Nkomo and Mugabe. In doing so, it sees their suspicions of, and participation in, the Anglo-American talks in these three years as being part of their own competition and rivalry to become the leader of a future independent Zimbabwe. The article then examines attempts by the Nigerians and the British to circumvent the Anglo-American talks to press for a direct settlement between Smith and the Patriotic Front in August 1978. The sources for this article are primarily from the Foreign and Commonwealth Office's Rhodesia Office files.